Bilateral Internal Thoracic Artery Configuration for Coronary Artery Bypass Surgery: A Prospective Randomized Trial. (July 2016) - Glineur, David; Boodhwani, Munir; Hanet, Claude; de Kerchove, Laurent; Navarra, Emiliano; Astarci, Parla; Noirhomme, Philippe; El Khoury, Gebrine
Abstract : Background—: Bilateral internal thoracic arteries (BITA) have demonstrated superior patency and improved survival in patients undergoing coronary artery bypass grafting. However, the optimal configuration for BITA utilization and its effect on long-term outcome remains uncertain. Methods and Results—: We randomly assigned 304 patients undergoing coronary artery bypass grafting using BITA to either in situ or Y grafting configurations. The primary end point was 3-year angiographic patency. Secondary end points included major adverse cardiac and cerebrovascular events (ie, death from any cause, stroke, myocardial infarction, or repeat revascularization) at 7 years. More coronary targets were able to be revascularized using internal thoracic arteries in patients randomized to Y grafting versus in situ group (3.2±0.8 versus 2.4±0.5 arteries/patient; P <0.01). The primary end point did not show significant differences in graft patency between groups. Secondary end points occurred more frequently in the in situ group ( P =0.03), with 7-year rates of 34±10% in the in situ and 25±12% in the Y grafting groups, driven largely by a higher incidence of repeat revascularization in the in situ group (14±4.5% versus 7.4±3.2% at 7 years; P =0.009). There were no significant differences in hospital mortality or morbidity or in late survival, myocardial infarction, or stroke between groups. Conclusions—: Three-year systematic angiographic follow-up revealed no significant difference in graft patency between the 2 BITA configurations. However, compared with in situ configuration, the use of BITA in a Y grafting configuration results in lower rates of major adverse cardiovascular and cerebrovascular events at 7 years. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01666366. Abstract : Supplemental Digital Content is available in the text.